Medicinal Cannabis in Reducing Physical and Psychological Problems Caused by Chemotherapy and Intestinal Inflammation; Advantages and Challenges (A Review) - Razieh Esmaeili; Reza Rostami (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: A key trigger for many of the complications that are symptoms of cancer types is changes in the gastrointestinal environment, which is a major obstacle in the way of managing side effects. The purpose of this research was to investigate the benefits and challenges of using medicinal cannabis in reducing physical and psychological problems caused by chemotherapy and intestinal inflammation as a review study. Methods: In this review study, a comprehensive search in English was conducted in reputable scientific databases such as PubMed, ProQuest, Google, Google Scholar, Scopus, Web of Science, and CINAHL from 2019 to 2023, using a combination of keywords to find relevant sources and studies. . Based on the established inclusion and exclusion criteria, and the removal of duplicate studies, texts relevant to the objectives of this study were extracted from a total of 81 reviewed articles. Results: The studies reviewed showed that the breakdown of the mucosal barrier (mucositis) was a common and primary side effect of cancer treatments, contributed to a wide range of severe physical and psychological symptoms such as diarrhea, nausea, vomiting, infection, malnutrition, fatigue, depression, and insomnia, for which medical cannabis may be effective in alleviating these symptoms. Conclusion: Considering the potential challenges and benefits of medicinal cannabis in reducing physical and psychological problems caused by chemotherapy and intestinal inflammation, it is necessary to investigate more research in this field and if more clinical evidence is confirmed, medicinal cannabis can be used as a treatment.